Enhancing academic literacies through EMI training:three perspectives on teaching towards the Certificatein EMI Skills at the University of São Paulo - Fonseca, Luciana Carvalho; Corbett, John Blair; Costa, Jose Alberto (Letras, 2022)
In many Brazilian universities, internationalization policies have led to increased pressure on academic staff to offer courses using English as a Medium of Instruction (EMI). In 2019, in order to offer support to staff adopting EMI, the University of São Paulo partnered with Cambridge Assessment English to pilot a Certificate course in EMI Skills. This partnership offers advantages but raises questions about the adaptation of a standardized international course and certificate in EMI skills for a specific institution. The present paper offers three perspectives on the pilot course – from the provider, an instructor, and the participants – and discusses their implications for USP and other Brazilian institutes of higher education.